2015
DOI: 10.1080/15332667.2015.1041352
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Impact of Relationship Marketing on Cross-Buying

Abstract: This article addresses the gap related to the role of relationship marketing in cross-buying and therefore aims to investigate the effect of quality of relationship marketing on cross-buying intentions in the Indian banking context. Five forms of relationship marketing were considered: relationship advertising, 2-way communications, database marketing, face-to-face contacts, and listening activities. The study also examined the indirect effect of quality of relationship marketing via relationship quality. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
0
3
0
1
Order By: Relevance
“…Để thấy được tác động của chất lượng mối quan hệ lên hành vi mua chéo, nhóm tác giả xem xét ảnh hưởng của từng thuộc tính trong mối quan hệ này. Nhiều nghiên cứu thực nghiệm chỉ ra rằng, sự tin tưởng của khách hàng đối với ngân hàng giúp gia tăng hành vi mua chéo các sản phẩm, dịch vụ tài chính (Lin, 2012;Vyas & Raitani, 2015. Soureli và cộng sự (2008) tìm thấy tác động trực tiếp của sự tin tưởng lên ý định mua chéo của khách hàng, trong khi đó, Liu và Wu (2009) cho rằng sự tin tưởng đóng một vai trò trung gian quan trọng trong việc mua chéo của khách hàng giữa các danh mục sản phẩm khác nhau trong dịch vụ ngân hàng.…”
Section: Mối Quan Hệ Giữa Sự Tin Tưởng Và Hành VI Mua Chéounclassified
“…Để thấy được tác động của chất lượng mối quan hệ lên hành vi mua chéo, nhóm tác giả xem xét ảnh hưởng của từng thuộc tính trong mối quan hệ này. Nhiều nghiên cứu thực nghiệm chỉ ra rằng, sự tin tưởng của khách hàng đối với ngân hàng giúp gia tăng hành vi mua chéo các sản phẩm, dịch vụ tài chính (Lin, 2012;Vyas & Raitani, 2015. Soureli và cộng sự (2008) tìm thấy tác động trực tiếp của sự tin tưởng lên ý định mua chéo của khách hàng, trong khi đó, Liu và Wu (2009) cho rằng sự tin tưởng đóng một vai trò trung gian quan trọng trong việc mua chéo của khách hàng giữa các danh mục sản phẩm khác nhau trong dịch vụ ngân hàng.…”
Section: Mối Quan Hệ Giữa Sự Tin Tưởng Và Hành VI Mua Chéounclassified
“…Research hypothesis Fan, Mattila, & Zhao (2015) indicated that an enterprise being able to rapidly respond to customer complaints would maintain customer loyalty; besides, rapid and proper service recovery could enhance customer satisfaction and loyalty and establish good word of mouth (Bowen & Chen, 2015). Accordingly, eff ective recovery strategies could eff ectively reduce customers' dissatisfactory emotion to the enterprise as well as enhance the satisfaction and brand loyalty to prevent customers from loss (Vyas & Raitani, 2015). Park & Ha (2016) indicated that bad service recovery would result in customers not being willing to continue the relationship with the enterprise to reduce profi ts and enhance business and management costs of the enterprise, because it required costs to strive for new customers.…”
Section: Establishment Of Research Hypothesis and Empirical Research mentioning
confidence: 99%
“…On the one hand, RM is much more efficient to create long-term relationship with customers (Palmatier, 2008) and RM has been proven to be a useful tool in improving relationship quality (Vyas & Raitani, 2015) as well as enhancing competitive advantage (Zinkhan, 2002) that will lead to customer retention (Berry, 1995). Furthermore, RM is also seen as a successful relational exchange that will enhance financial performance, satisfaction, learning, propensity to stay, acquiescence and decrease uncertainty (Hunt, Arnett & Madhavaram, 2006).…”
Section: Review Of the Literature Relationship Marketing Orientation (Rmo)mentioning
confidence: 99%